Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.pone.0048698
|View full text |Cite
|
Sign up to set email alerts
|

Repellents Inhibit P450 Enzymes in Stegomyia (Aedes) aegypti

Abstract: The primary defence against mosquitoes and other disease vectors is often the application of a repellent. Despite their common use, the mechanism(s) underlying the activity of repellents is not fully understood, with even the mode of action of DEET having been reported to be via different mechanisms; e.g. interference with olfactory receptor neurones or actively detected by olfactory receptor neurones on the antennae or maxillary palps. In this study, we discuss a novel mechanism for repellence, one of P450 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Such activity has been reported in EOs from sesame, Amyris , sandalwood, Helichrysum , cedar wood, and black pepper that exhibited synergistic effects in Aedes aegypti (Diptera: Culicidae) larvae while inhibiting cytochrome P450 monooxygenases and/or carboxylesterases in vitro [ 16 ]. Reduced esterase, glutathione-S-transferase, and/or monooxygenase activity following exposure to various EOs was similarly reported in other pests [ 46 – 49 ], and probably accounts for synergism of imidacloprid in several of our bioassays. This is significant given reports of M .…”
Section: Discussionsupporting
confidence: 78%
“…Such activity has been reported in EOs from sesame, Amyris , sandalwood, Helichrysum , cedar wood, and black pepper that exhibited synergistic effects in Aedes aegypti (Diptera: Culicidae) larvae while inhibiting cytochrome P450 monooxygenases and/or carboxylesterases in vitro [ 16 ]. Reduced esterase, glutathione-S-transferase, and/or monooxygenase activity following exposure to various EOs was similarly reported in other pests [ 46 – 49 ], and probably accounts for synergism of imidacloprid in several of our bioassays. This is significant given reports of M .…”
Section: Discussionsupporting
confidence: 78%
“…AChE and MFO activity in all of the treated Ae. aegypti strains in this study reduced when compared to the controls, as recorded after exposure to P. crispum essential oil for 24 h. Similar results of reduced activity of AChE [37,90,91] and MFO [22,26,92,93,94] were observed in several insect species exposed to different botanical products. These findings were contrary to those in many studies, which demonstrated biochemical responses with elevation of AChE or MFO activity after treatment with either synthetic substances or plant products.…”
Section: Discussionsupporting
confidence: 87%
“…In a study by Joffe and colleagues, parsley seed oil and dillapiole oil where found to inhibit cytochrome P450 activity, but not esterase activity, providing a synergistic effect for pyrethrum on Musca domestica [ 108 ]. In mosquitos, several groups have reported on PDPs and inhibition: plant flavanoids are potent inhibitors of CYP6Z2; thymol and eugenol appear to inhibit both cytochrome P450 and Glutatione S-transferase activities; and essential oils of several native Columbian plants that possess repellent activity are inhibitors of cytochrome P450 activity [ 115 - 117 ].…”
Section: Reviewmentioning
confidence: 99%